2022
DOI: 10.1021/acs.jpcc.2c04521
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thermally Activated Quenching and Energy Migration in Luminescence of Silver Clusters in Glasses

Abstract: Luminescent silver clusters stabilized in different hosts represent an important class of new luminophores with numerous potential applications. Nevertheless, there are a lot of open questions regarding the emission mechanism of the clusters. In this work, luminescence properties of silver clusters in a silica-based glass were analyzed by using steady-state and time-resolved spectroscopy. The obtained results suggest that deactivation of cluster excited states does not include cluster interaction and should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…This result may suggest that fluorescence and phosphorescence at least partially originate from the different centers in the glass. The interpretation contradicts with the previously published results on the mutual temperature dependence of fluorescence and phosphorescence [4,50,51] . Also, it was shown that introduction of lanthanide ions uniformly quenches luminescence of silver clusters in glasses without spectral selectivity, [35,39,52] which is unlikely in the case of several different emissive centers.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…This result may suggest that fluorescence and phosphorescence at least partially originate from the different centers in the glass. The interpretation contradicts with the previously published results on the mutual temperature dependence of fluorescence and phosphorescence [4,50,51] . Also, it was shown that introduction of lanthanide ions uniformly quenches luminescence of silver clusters in glasses without spectral selectivity, [35,39,52] which is unlikely in the case of several different emissive centers.…”
Section: Resultscontrasting
confidence: 60%
“…The interpretation contradicts with the previously published results on the mutual temperature dependence of fluorescence and phosphorescence. [4,50,51] Also, it was shown that introduction of lanthanide ions uniformly quenches luminescence of silver clusters in glasses without spectral selectivity, [35,39,52] which is unlikely in the case of several different emissive centers. Heat treatment after irradiation restores the original emission shape with a dominant phosphorescence peak (Figures 4c, 4d) revealing the reversible character of photobleaching.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the short-lived emission spectra of Ag.05 and Ag.01 shows that the fluorescence of Ag.05 was wider and tailed more to the longer wavelength region (Figure 2d). The combination of fluorescence and phosphorescence with emission in blue and green-yellow parts of the spectra is a characteristic feature of the luminescence of silver clusters in the studied glass matrix [24,37]. Additionally, we observed a decrease in the fluorescence lifetime to 16.9 ns, which may originate from the contribution of silver clusters, since the fluorescence lifetime of silver clusters in the studied glass varies from 3.2 to 4.5 ns.…”
Section: Resultssupporting
confidence: 52%
“…The most prominent difference in the value of luminescence quantum yield partly originates from the passive absorption at the excitation wavelength since the formation of clusters in ion-exchange layers does not require the cerium in glass composition. The ion exchange procedure used to form silver clusters in photo-thermo-refractive glass provides an average Ag 2 O concentration of 5.2 mol.% in a 12.4 µm layer with a surface concentration of 12.7 mol.% [24]. Therefore, the concentrations of silver ions used to form luminescent silver clusters in the glass bulk were 200-500 times lower than in the ion exchange method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation